RETRACTED ARTICLE: E-Blue: Implementation of an Integrated Blue Economy Ecosystem to Increase Coastal MSMEs Competitiveness - Perdana, Tito Aditya; Purusa, Nanda Adhi; Kurniawan, Rudi; Suryawijaya, Tito Wira Eka (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objectives: This study aims to determine the implementation and the right business strategy for sustainable fisheries that adopt the "E-Blue" blue economy ecosystem model. Background Problems: The challenges faced in developing a booming blue economy emphasize the need for strong commitment and collaboration between central and regional governments, to support overall development. The background problems also recognize technology’s impact on the activities of micro, small and medium enterprises (MSMEs) and stress the significance of quick responses to these changes. Novelty: This lies in the study’s exploration of the role of digital transformation in sustainable fisheries within the blue economy framework. It emphasizes the need for commitment, innovation, and technological adaptation to ensure the success of blue economy-based development. Research Methods: This qualitative study adopts a narrative approach to gather data on sustainable fisheries strategies aligned with the blue economy ecosystem model. The research utilizes this approach to gain insights into the development possibilities for the research object. Finding/Results: The study's findings highlight the crucial role of the government’s commitment and decisive actions for the successful development of the blue economy in the fisheries sector. The study underscores the potential of digital transformation as a bridge between stakeholders and consumers, enabling efficient supply chain management and diverse product processing for community welfare. Conclusion: The study concludes that successful blue economy development relies on strong collaboration between governments, innovative policy programs, and swift responses to technological changes. The study emphasizes the importance of continuous innovation to enhance competitiveness and market access in Indonesia's fisheries sector.